Glycerol Production by the Yeast Saccharomyces cerevisiae and its Relevance to Wine: A Review - Scanes, K.T.; Hohrnann, S.; Prior, B.A. (South African Journal of Enology and Viticulture, 2017)
Glycerol is a sugar alcohol produced as a by-product of the ethanol fermentation process by Saccharomyces cerevisiae. In wines, levels between 1 and 15 gll are frequently encountered and the higher levels are thought to contribute to the smoothness and viscosity of wine. Glycerol and ethanol levels are inversely related, which may add an additional favourable attribute to wine. The metabolic pathways involved in glycerol synthesis, accumulation and utilisation by yeast are now better understood since a number of the genes involved in glycerol metabolism have been cloned, sequenced and their functions established. These fundamental studies now permit the glycerol levels produced by yeast to be raised by either the specific control of the culture conditions or by the manipulation of the genetic and molecular properties of the yeast. In some instances, the level of glycerol produced under laboratory conditions has been significantly raised. However, a number of undesirable by-products also accumulate during the fermentation and an improved understanding of the glycerol metabolic flux is required before wines with a consistently elevated glycerol concentration can be produced.